Coping With Oral Tongue Cancer and COVID-19 Infection - De Berardinis, Rita; Guiddi, Paolo; Ugolini, Sara; Chu, Francesco; Pietrobon, Giacomo; Pravettoni, Gabriella; Mastrilli, Fabrizio; Chiocca, Susanna; Ansarin, Mohssen; Tagliabue, Marta (Frontiers in Psychiatry, 2021)
To date, April 19th, 2021, the coronavirus disease 2019 (COVID-19) caused about 140.886.773 confirmed cases and more than 3.000.000 deaths worldwide since the beginning of the pandemic. Oncology patients are usually frail due to the fear of prognosis, recurrence and outcomes of treatments. Thus, coping with cancer is a complicated process that is necessary to overcome oncological challenge, even more in case of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) disease. This is a brief case report on a middle-aged man affected by advanced oral tongue cancer and COVID-19, describing his experience of cancer diagnosis, surgical treatment and rehabilitation during the hospital quarantine for COVID-19. Besides the traumatic experience due to the functional alteration in breathing, eating and speaking caused by major surgery and the concurrent facial disfigurement, our patient had to face a COVID-19 diagnosis, which implied hospital and social isolation. The aim of this perspective work is to focus on the role of the psychological support in the management of hospital distress related to COVID-19 psychophysical loneliness or alienation. In our experience such support should anticipate patients’ oncological surgery or treatment and should be implemented through telemedicine in case of isolation or after hospital discharge.